2002
DOI: 10.4315/0362-028x-65.8.1271
|View full text |Cite
|
Sign up to set email alerts
|

Heat Resistance of Juice Spoilage Microorganisms

Abstract: The heat resistance of various yeasts (Saccharomyces cerevisiae, Rhodotorula mucilaginosa, Torulaspora delbrueckii, and Zygosaccharomyces rouxii), molds (Penicillium citrinum, Penicillium roquefortii, and Aspergillus niger), and lactic acid bacteria (Lactobacillus fermentum and Lactobacillus plantarum) obtained from spoiled acid or acidified food products was determined in 0.1 M citrate buffer at pH values of 3.0, 3.5, and 4.0. S. cerevisiae was the most heat resistant of the microorganisms in citrate buffer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 18 publications
1
52
0
1
Order By: Relevance
“…Ryu and Beuchat (48) reported increased heat resistance in acid-adapted E. coli 0157:H7 in heat-treated fruit juices. Shearer et al (51) reported that the heat resistance of S. cerevisiae obtained from spoiled acidic products was higher in fruit juices than in citrate buffer. Increased resistance to organic acids, which are used as preservatives, after weak acid adaptation was reported in S. cerevisiae (44,65).…”
Section: Resultsmentioning
confidence: 98%
“…Ryu and Beuchat (48) reported increased heat resistance in acid-adapted E. coli 0157:H7 in heat-treated fruit juices. Shearer et al (51) reported that the heat resistance of S. cerevisiae obtained from spoiled acidic products was higher in fruit juices than in citrate buffer. Increased resistance to organic acids, which are used as preservatives, after weak acid adaptation was reported in S. cerevisiae (44,65).…”
Section: Resultsmentioning
confidence: 98%
“…When suspended in a strawberry-based medium, D. hansenii cultivated in a liquid growth medium was also found to be less heat resistant than its S. cerevisiae counterpart (TruongMeyer, Strehaiano, & Riba, 1997). Furthermore, S. cerevisiae was similarly established to be more heat resistant compared to a number of juice spoilage yeasts (T. delbrueckii, Rhodotorula mucilaginosa, Zygosaccharomyces rouxii), molds (Penicillium roquefortii, Aspergellus niger) and lactic acid bacteria (Lactobacillus fermentum, Lactobacillus plantarum); and was identified as an appropriate challenge organism in establishing thermal processes for acidic products (Shearer, Mazzotta, Chuyate, & Gombas, 2002). The heat inactivation rate of the composite yeast species was greater than most of the yeasts but was 4 times smaller than that of S. cerevisiae.…”
Section: Heat Inactivationmentioning
confidence: 98%
“…13 This feature allows L. plantarum to grow easily in juice drinks. 14 In fact, it may metabolize citric and malic acids present in fruit juices and fruit drinks, reducing the acidity of the product.…”
Section: Introductionmentioning
confidence: 99%